State and Trends of the Carbon Market 2006 : Update, January 1-September 30, 2006 - Capoor, Karan; Ambrosi, Philippe (World Bank, Washington, DC, 2013)
Carbon transactions are defined as purchase contracts or ERPAs (Emission Reductions Purchase Agreements) whereby one party pays another party in return for greenhouse gas (GHG) emissions reductions that the buyer can use to meet its compliance or corporate citizenship - objectives vis-a-vis GHG mitigation. Payment is made using one or more of the following forms: cash, equity, debt, or in-kind contributions. This paper includes the following headings: executive summary; methodology; allowance-based markets; project-based markets; investment climate and regulatory environment; and regulatory outlook.